2014
DOI: 10.1364/oe.22.022794
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber dual wavelength passive Q-switched fiber laser using a dispersion-decreasing taper fiber in a nonlinear loop mirror

Abstract: This paper describes a proposal and successful demonstration of a dual wavelength all-fiber passively Q-switched erbium-doped fiber ring laser. The Q-switch operation was realized by using a nonlinear loop mirror that incorporated an unbalanced dispersion-decreasing taper fiber to act as a saturable absorber without additional elements. This setup enabled a fiber ring laser to achieve a performance of 48.7 kHz repetition rate with pulse duration of around 3.2 μs and approximate pulse energy of 20 nJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…It is worthwhile that the efficiency of the dual-wavelength Q-switched laser based on the cavity suggested by us is somewhat higher than the values achieved with the other generation methods [2,16] and close to those reported in Refs. [1,4]. We have studied the pulse patterns for each of the lasing modes, using a tunable bandpass filter (Newport TBF-1550-1) at the output.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile that the efficiency of the dual-wavelength Q-switched laser based on the cavity suggested by us is somewhat higher than the values achieved with the other generation methods [2,16] and close to those reported in Refs. [1,4]. We have studied the pulse patterns for each of the lasing modes, using a tunable bandpass filter (Newport TBF-1550-1) at the output.…”
Section: Resultsmentioning
confidence: 99%
“…Dual-wavelength Q-switched light generation usually involves different nonlinear optical methods, e.g. those based on birefringence with saturable absorption or nonlinear polarization rotation with saturable absorption [1][2][3][4]. One of the methods for the dual-wavelength laser generation, which is based on so-called D-fibres, offers the ability to control multi-modal interference.…”
Section: Introductionmentioning
confidence: 99%
“…Different experimental setups of DWFL by passive Q-switching technique have been reported [39][40][41]. However, to our knowledge, there have not been reported approaches using EYDCF as a gain medium.…”
Section: Q-switched Fiber Lasers: a Review From Operating Principle Tmentioning
confidence: 99%
“…Concerning cavity losses adjustment for dual wavelength laser operation, the most frequent method is the use of PC in ring cavity fiber lasers. H. Ahmad et al [40] reported a ring cavity passive Q-switched DWFL operating at 1557.8 nm and 1559 nm by using PC for dual wavelength generation. A nonlinear optical loop mirror (NOLM) with a dispersion-decreasing taper fiber (DDTF) in the fiber loop is used as a passive Q-switching element.…”
Section: Q-switched Fiber Lasers: a Review From Operating Principle Tmentioning
confidence: 99%